From functional food to inflammatory and metabolic regulation: A systematic review of the effects of Okra (Abelmoschus esculentus) consumption in various processed preparations - Mike Permata Sari; Cityta Putri Kwarta; Afifa Radhina; Nurul Ain (PT WIM Solusi Prima, 2026)
Okra (Abelmoschus esculentus) is a horticultural crop containing phytochemicals that have the potential to provide health benefits. Several studies have shown that okra consumption can affect the levels of metabolic modulators, oxidative stress, and inflammatory biomarkers. Therefore, this systematic review aims to comprehensively evaluate the scientific evidence regarding the effect of okra consumption on metabolic and inflammatory parameters based on the type of okra and the type of okra preparation. This study is a systematic review that follows the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines, a literature search was conducted in five electronic databases. The article selection process was carried out using the PICOS framework, while the methodological quality was assessed using the Cochrane Risk of Bias (RoB 2) approach. Data were analyzed descriptively due to heterogeneity of study designs that precluded meta-analysis. A total of 124 articles were identified in the initial search phase after removing duplicates. After title and abstract screening, 51 studies met the inclusion criteria and were included in the analysis. Risk of bias assessment indicated that most studies had a low risk of bias in almost all domains assessed. The synthesis results indicate that okra consumption has the potential to have positive effects on lipid profiles, glycemic control, and modulation of inflammatory and oxidative stress biomarkers.